The impact of infused health drinks packaging design on consumer / Nur Shakirah Mohd Shukri - Mohd Shukri, Nur Shakirah (2015)
The purpose if this research is to identify and analyze the effect of visual design on the label packaging design infused health drinks on consumer. Packaging plays important role for storage, protection for its taste,smell,look, provide relevant information and to influence consumer to purchase the product as consumers buy range of goods every day in the variety of packaging materials. Without packaging, the drinks will be easily affected by bacteria and other unwanted chemicals that can cause bad effect on its content and consumers health. Nowadays, there are many types of packaging in the market like paper, aluminum, plastic,wood, board,steel and especially glass as the infused drinks is placed in the jar. Packaging design is one of the key elements of marketing strategy for a product as it is the visual face that will be promoted and recognized by the customer.